Interpersonal Relations and Non-Academic Achievement among University Upgrading (Grade V) Teacher Students - Amongin, Helen; Baguma, Peter; Oonyu, Joseph; Lassen, Emeritus (International Journal of Online and Distance Learning, 2024)
Purpose: Given the challenges faced by distance and life-long education students engaging in non-academic activities, combined with the common assumption that adults are good at interpersonal relations, this study explores the relationship between interpersonal relations (IR) and non-academic achievement (NAA) in Ugandan universities. Methodology: This was a qualitative study. Data included a population of teacher students from Makerere University and Uganda Christian University, Mukono and a sample of 75 upgrading Grade V teacher students from Makerere University and Uganda Christian University, Mukono, obtained through purposive sampling technique, The Researcher formulated (vetted by 07 Professors and pilot tested) Group interviews, an observation schedule for the students' sample, and in-depth interviews for Lecturers were used to collect data. Findings: Data was presented using tables, graphs and figures. Results showed that positive interpersonal relations were very critical in non-academic activities and thus positively influenced achievement among university upgrading (Grade V) teacher students. Data analysed using NVIVO showed that interpersonal relations were very important in terms of team spirit, group work, field activities and collegial relations. In conclusion, strengthening interpersonal relations is very important in the 21st century with research stressing collaborative approaches. The practical non-academic activities not only refresh the body but enhance positive interactions that are useful in the NAA for common purpose and goals in life. Unique Contribution to Theory, Practice and Policy: As a contribution to policy and practice, the study suggests that teachers need to have an all-round curriculum for training interpersonal relations for better non-academic achievement. Knowledge of negative and positive perceptions of interpersonal relations is critical for learning, training, field activities and research. Ministry of Education and Sports thus, needs to be intentional in including aspects of interpersonal relations and non-academic achievement at higher educational institutions and universities. Interpersonal relations and self-determinism theories need to be made more relevant in universities.